Peran Dosen Dalam Pelatihan Pembukuan UMKM di Kecamatan Balikpapan Tengah - Yuliani, Tutik; Susilowati, Dwi; Sari, Dika Karlinda; Anam, Hairul; Saraswati, Wiwik; Yusuf, Tamzil; Fajar, Ichsan; Firdaus, Dzaky (Abdimas Universal, 2025)
The bookkeeping training for MSMEs in Balikpapan Tengah District aims to improve the understanding and skills of MSMEs groups in calculating, recording, bookkeeping, and managing business finances. This training is expected to help the development of MSMEs, ultimately enhancing competitiveness and community welfare. The activities were carried out through training and mentoring using the siApik application, starting with a survey of participants who own or mentor MSMEs in the district. The results of the training are expected to improve participants' skills in structured financial bookkeeping and to enhance their understanding of using the siApik application to boost MSMEs performance.